MBARU NIANG DALAM PERSPEKTIF ETNOMATEMATIKA DI KAMPUNG RUTENG PU’U - Muliani, Melita Moira; Makur, Alberta Parinters; Kurnila, Valeria Suryani; Sutam, Inosensius (Universitas Papua, 2020)
This study aimed to reveal how the Manggarai community used mathematical concepts in making the traditional house (Mbaru Niang) roof of Manggarai people and what were the mathematical concepts contained in it. This research used a qualitative approach with ethnographic methods. The selection of subjects in this study used purposive sampling technique. Data obtained by interviewing, observing and documenting. The validity of the data is supported through theory and facts in the field and also through expert judgment. The results showed that in the stages of the process of making the traditional house roof of Manggarai there were 3 activities that had a mathematical nuance namely designing, numerating and measuring and the mathematical concepts contained in the traditional house roof were the concept of the shapes namely triangles, rectangles, trapezoid and circles, the concept of distance, the concept of parallel lines, and lines and the pyramid.